(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Awake craniotomy poses a unique challenge to anaesthesiologists, and its success is highly dependent on careful patient selection and the experience of the surgical and anaesthesia team. I report the pre-operative preparation and anaesthetic management for resection of an intra-cerebraltumour by awake craniotomy in a 40 years old male patient for the first time done at CMH Dhaka. The challenges of sedation and psychologicalcare throughout the procedure are discussed. I conclude that the procedure can be performedsafely. Journal of Bangladesh Society of Anaesthesiologists 2015; 28(1): 43-45